Kebun Raya Banua medicinal plant species of the Fabaceae family as popular scientific books: Practicality test - Rema Yulianti; Muhammad Zaini; Danang Biyatmoko (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
Education in the 21st century is required to produce generations who have and master various kinds of skills, one of which is critical thinking skills. Therefore, learning is needed that can prepare students to think critically. One of them is applying local potential-based learning resources developed in popular scientific book teaching materials. This study aims to examine the practicality of the content, the practicality of expectations, and the actual practicality of the popular scientific books developed. The method used is based on Tessmer's formative evaluation design. The results of the research on the readability test obtained results of 87.18% with very good criteria, based on student responses, the results were 89.60% on the practicality of expectations and 92.59% on the actual practicality with very practical criteria, and based on the implementation of popular scientific books that developed which got the results of 92.59% on the implementation of expectations and 96.69% on the actual implementation with a very good category. This result shows that a popular scientific book titled